Cupping Care Effectiveness on Flection Range of Motion - Achmad Sya’id; Anita Fatarona (Universitas STRADA Indonesia, 2020)
This study aims to nalyzing whether cupping is effective in increasing the flection range of motion of low back pain clients. Methods: This study is quassy experimental with one group pre-post test design, cupping care was carried out by a certified nurse giving therapy during the pandemic. This study using 30 acute low back pain clients. ROM was measured before and 15 minutes after cupping care was given. Before cupping 96.7% flection ROM was on 3th degree, 15 minutes after cupping care, the flection ROM of 96.7% respondents increased to 4th. Analysis: using the Wilcoxon test, P value is (0.000) smaller than alpha (0.05). Based on the study the changes of flection ROM are significant due to the increase in endogenous opiates such as endorphins, encephalins, and dinorphins in the body. The opiate is produced during cupping care, so that the concentration of tension decreases and the blood flows properly